(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2019)
Conventional energy sources like coal, nuclear energy sources, water, and other fossil fuels are getting depleted day by day. The availability of these resources is limited and would be exhausted one day. Therefore people have recently started to use renewable energy sources like sun, wind and tidal energy for electrical power generation. The electricity generators which are mounted within the premises of consumers or in the vicinity of load are known as Distributed Generation resources. One of the abundant available energy resources is sun. The sunlight available from sun as expected would last for millions of years. The sunlight can be converted to electrical energy using Photovoltaics. The PV Panels mounted on the rooftops can convert sunlight to electrical energy. These PV panels contain small devices called as solar cells. The PV source is also connected to the utility grid through suitable Power Electronic Interfaces. The PV panels are distributed randomly in each phase. Sometimes the power from PV source in one phase can exceed the power generated from the grid in that phase. This excess power can flow from the point of common coupling towards the substation and can cause unbalance in the three phase currents of the transmission line. This Paper outlines a technique wherein a Distributed Static Compensator (DSTACOM) is connected to the grid which will take the unbalanced three phase currents of the transmission line, process the currents and inject currents back in the transmission line so as to make the three phase currents balanced, thus balancing the three phase power.